William McIlwaine and the 1859 Revival in Ulster: A Study of Anglican and Evangelical Identities. Issue 4 (11th September 2014) - RITCHIE, DANIEL
<x content-type="archive" xml:space="preserve">Abstract</x> The Evangelical awakening which took place in the province of Ulster during 1859 was one of the most important events in the religious history of the north of Ireland. Although it has received virtually uncritical acceptance by modern Evangelicals in Northern Ireland, few are aware that there was a significant minority of Evangelicals who dissented from offering the movement their wholehearted support. This article examines why one of nineteenth-century Belfast's most controversial Anglican clerics, the Revd William McIlwaine, was very critical of the movement. Not all critics were outright opponents of the revival, however. McIlwaine was one of the revival's moderate critics, who believed that it was partially good. Nevertheless, the awakening's physical manifestations and its impact on theology and church order deeply disturbed him. The article also explains why 1859 was a turning point in McIlwaine's ecclesiastical career, which saw him move from Evangelicalism to a moderate High Church position.